Motor Vehicle Tax Fiscal Incentives, Tax Socialization, And Electronic One-Stop Administration Services Office Influence On Taxpayer Compliance With Taxpayer Awareness - Bahari, Yuda Rian; Herawaty, Vinola (Green Publisher Indonesia, 2023)
This study aims to examine and analyze the effect of fiscal incentives for motor vehicle taxes, tax socialization, and the e-samsat system on taxpayer compliance with taxpayer awareness as a moderating variable during the Covid-19 pandemic. The data used is primary data in the form of a questionnaire given to respondents to answer. The sample method uses a purposive sampling technique. Of the active vehicle population in the South Jakarta city area, there are 1,182,322 taxpayers, based on calculations using the slovin formula, 100 taxpayers are taken. The analytical method used in this study is moderated regression analysis (MRA). The results of hypothesis testing show that fiscal incentives have a significant positive effect on taxpayer compliance, tax socialization has a significant positive effect on taxpayer compliance, the e-samsat system has no significant positive effect on taxpayer compliance, taxpayer awareness has a significant positive effect on taxpayer compliance, awareness taxpayers do not strengthen the effect of fiscal incentives on taxpayer compliance, taxpayer awareness does not strengthen the effect of tax socialization on taxpayer compliance, and taxpayer awareness does not strengthen the effect of the e-samsat system on taxpayer compliance.